Search for pair-produced three-jet resonances in proton-proton collisions at √s=13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Babaev A. A. Anton Anatoljevich (2019, 2019)
Title screen